What is Dengue? - Jorge R. Rey (EDIS)
ENY737, a 5-page illustrated fact sheet by Jorge R. Rey, describes this human disease caused by a virus transmitted by mosquitoes. It describes the viruses, the vectors, the disease and its history. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2007.